Wealth after work : innovative reforms to expand retirement security - Gale, William G.; Iwry, J. Mark; John, David C. (Brookings Institution Press, 2021)
"Pensions and retirement saving plans have helped millions of households build financial security. But tens of millions of people have been left behind, without access to these wealth accumulation vehicles. For many others, the plans they have do not ensure financial security in retirement. The problems that underlie these failures can be addressed. This book proposes concrete, practical ways to make dependable retirement income accessible for all Americans-not just those with means. Individual accounts have eclipsed traditional pensions as the primary vehicle for retirement saving in the United States-a shift that underlies many sources of retirement insecurity. The 401(k) plan and similar accounts have increased financial security for many people but have done nothing for millions more. Many of those who do have such plans are burdened with the need to make numerous saving, investment, and withdrawal decisions that stress their financial acumen. Financial advice that is unbiased, unconflicted, and affordable is often difficult to find. Managing wealth in retirement-especially the need to convert retirement savings into steady income-poses significant challenges that current financial instruments and practices do not adequately address. Economic downturns like the Great Recession and the COVID-19 pandemic increase financial insecurity and make addressing these issues more urgent. Written by noted experts in the field, Wealth After Work offers practical solutions that address these concerns. The proposals show how policymakers can help all Americans gain access to retirement savings accounts, obtain better information about their savings choices, and better manage their wealth in retirement. By proposing solutions that build on, rather than replace the existing system, the book provides a nuanced, practical guide to reform that would benefit all Americans"--